2009
DOI: 10.1242/dev.028472
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans mig-6encodes papilin isoforms that affect distinct aspects of DTC migration, and interacts genetically withmig-17andcollagen IV

Abstract: The gonad arms of C. elegans hermaphrodites acquire invariant shapes by guided migrations of distal tip cells (DTCs), which occur in three phases that differ in the direction and basement membrane substrata used for movement. We found that mig-6 encodes long (MIG-6L) and short (MIG-6S) isoforms of the extracellular matrix protein papilin, each required for distinct aspects of DTC migration. Both MIG-6 isoforms have a predicted N-terminal papilin cassette, lagrin repeats and C-terminal Kunitz-type serine protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 36 publications
2
82
0
Order By: Relevance
“…Thus, it is possible that EMB-9 may mediate FBL-1 function to promote integrin expression and cytoskeletal rearrangement in DTCs, which are required for gonadal elongation. In support of this, RNAi knockdown of ina-1 and ts let-2 and emb-9 mutants reared at nonpermissive temperatures exhibit the short-arm gonad phenotype (Cram et al 2006;Meighan and Schwarzbauer 2007;Kawano et al 2009) similar to that observed in fbl-1(tk45) mutants.…”
Section: Emb-9(tk75) May Affect Interactions Between Nc1 Domainsmentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, it is possible that EMB-9 may mediate FBL-1 function to promote integrin expression and cytoskeletal rearrangement in DTCs, which are required for gonadal elongation. In support of this, RNAi knockdown of ina-1 and ts let-2 and emb-9 mutants reared at nonpermissive temperatures exhibit the short-arm gonad phenotype (Cram et al 2006;Meighan and Schwarzbauer 2007;Kawano et al 2009) similar to that observed in fbl-1(tk45) mutants.…”
Section: Emb-9(tk75) May Affect Interactions Between Nc1 Domainsmentioning
confidence: 53%
“…A temperature-sensitive (ts) embryonic lethal allele of emb-9, g34 , did not exhibit gonadal elongation defects at 20°, an intermediate temperature that results in growth retardation: 50% of g34 larvae and 100% of wild-type larvae shifted from 16°to 20°at the first larval stage (L1) grew to be adults after 48 hr (n = 80). Shifting mutant L2 larvae to 25°, a restrictive temperature, resulted in severe gonadal defects (100% of both anterior and posterior gonad arms; n = 20) as reported (Kawano et al 2009). g34 could not suppress the fbl-1(tk45) mutants at 20° (Figure 2A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent work in C. elegans has shown that the conserved matrix component fibulin is required to preserve collagen in both the gonadal and intestinal tissues -loss of fibulin does not affect collagen function during embryogenesis or early larval development, but does result in the loss of collagen during the end of larval development (Kubota et al, 2012). This loss of collagen is thought to underlie the shortened and widened gonad seen in fibulin mutants, as this phenotype can be recapitulated by shifting a temperature-sensitive collagen mutant to the restrictive temperature following embryogenesis (Kawano et al, 2009;Kubota et al, 2012). Taken together, these data indicate that there are numerous mechanisms that have evolved to regulate collagen incorporation, function and maintenance in basement membranes.…”
Section: Collagen Within Basement Membranes Constricts and Contours Tmentioning
confidence: 99%
“…Functions of some TSR proteins include stimulation of migration; others mediate adhesion or breakdown of the ECM. Papilin and ADAMTR, two TSR proteins, have reciprocal roles in Drosophila gastrulation [66], and other members of the superfamily have complementary functions in early nematode development [67].…”
Section: Extracellular Matrices Diploblasty and Triploblastymentioning
confidence: 99%